Body composition analysis using air displacement plethysmography - Ma, Chuan-Hsiao Peter (Department of Medicine, 2024)
In modern times, preventative medicine has become a major international focus. Body composition analysis and in particular the estimation of the percentage of body fat is an important tool for disease management. The percentage of body fat has the potential to be a tool health practitioners can use to suggest lifestyle and dietary changes that can help prevent disease. The approach taken in devising a low cost body composition measuring device is the principle of plethysmography. This approach measures the density of an object by measuring the volume of air the object displaces as well as the objects mass. A principle assumption of this approach is the validity of the two Component Model of body composition (2C Model). The model states that the human body can be split into two components of constant density: Fat (which has a measured density of 0.9 glcni3) and Non-fat tissue (which has a measured density of 1.1 g I cm3 ). The validity of the 2C model allows an Individual's body fat percentage to be determined following the calculation of that Individual's body density. According to the 2C model, a person who has a density of 1.06 g/cm3 (according to the 2C Model) has 15% of body fat. This dissertation investigates other methods of body fat determination and suggests why air displacement plethysmography (ADP) is the best solution for the alms of the project. A theoretical analysis of ADP has indicated that the volume needs to be determined to an accuracy of within 200 ml for a ± 2% precision in body fat estimation. This model also demonstrates how this Initial goal can be achieved with in vivo studies. The various parameters of the model are examined to determine the sensitivity of % body fat estimation to various errors of measurement in each respective parameter. A low cost ADP device that measures the volume of an unknown test object has been constructed based on the theoretical model. This device consists of a measuring chamber and a reference chamber. Each connects to a motor driven piston pump. The pressure difference between the chambers is sensed and calibrated with known test volumes in the measuring chamber. After calibration the volume of unknown objects can be determined from the pressure differential using the correlation equation. The constructed ADP device provides repeatable ± 300ml precision on Inanimate objects. Using the 2C model, this accuracy in volume measurement results in a 3% inaccuracy in the determination of body fat percentage. Although this error is not low enough for a biologically meaningful result in body composition analysis, the major factors that cause error have been identified and Investigated. In particular, it has been found that the piston pump frequency must be stable and constant within 0.06rpm. The recommendation for further development therefore is that a stepper motor driven piston or a precision loud speaker system be used to compress the air in the chambers, at a precise and constant frequency. Theoretical investigations reveal that these will allow accuracy of the volume measurement to be within 200 ml. A solid foundation has been established for a low cost device. The total cost of this device including future development Is estimated to be less than 10% of the existing commercial devices. This will provide a practical tool for medical practitioners involved in preventative medicine, and will also allow interventional procedures to be monitored and assessed.